PEMBINAAN THAHARAH SESUAI DENGAN KAIDAH FIQIH PADA SANTRI TPA BAITUL ULUM DESA NANGA KALIS - Andi Supriandi; Riyanto, Meli Agustin, Putri Maya, Yuyun Novitasari, Aulia Yunara, Risa Susanti, Nopitasari, Essy Pu (Adiba Aisha Amira, 2026)
This study examines the development of thaharah, particularly wudu according to fiqh principles, for students at TPA Baitul Ulum in Nanga Kalis Village. Initial observations revealed low understanding among 6-11 year old students regarding wudu procedures and prayer recitation. Employing a qualitative descriptive method with an field research approach, the program was conducted on December 17-21, 2025, through preparation, planning, interactive lectures, and practice stages. Data collection involved participatory observation, interviews, and documentation. Evaluation results indicated improved student participation and enthusiasm, effective guidance from PKL students, despite challenges in facilities, funding, time, and varying abilities, which were addressed via flexible approaches. In conclusion, the program successfully enhanced students' thaharah skills, reinforcing physical-spiritual purity, with recommendations for sustained support to TPA programs.